Cucuteni-Tripolje, Ukraine. Herausbildung hierarchisch gegliederter Siedlungslandschaften im späten 5. und 4. Jt. v. Chr. - Rassmann, Knut (e-Forschungsberichte des DAI, 2023)
The emergence of a large settlement in the 4th millennium BC in Eastern Europe marks a new level of ancient European sedentary life. Large-scale geomagnetic prospection revealed clear settlement structures of hundreds of houses, regularly arranged in space. This appears to have also mirrored the social structures which existed within the settlements. The dimension of the settlements requires new fieldwork concepts. Based on the details of architectural features like houses, kilns and storage pits revealed by these prospections, small scale excavation in different areas of the settlement were undertaken to detect differences and similarities between house groups. The excavations were multidisciplinarily founded to reconstruct the process of the rise and decline of settlements in the context of human-environment interactions.